2021
DOI: 10.1088/1361-6501/abf178
|View full text |Cite
|
Sign up to set email alerts
|

On the role of excitation pulse duration on luminescence measurements

Abstract: Described here is an investigation into the effects of excitation pulse duration on the temporal character of luminescence of three characteristic thermographic phosphors: Mg4FGeO6:Mn, La2O2S:Eu, and YAG:Dy. Attention is first given to the build-up of the emission while the excitation pulse is on and its relation to temperature. Next, effects after pulse termination are addressed. For emission comprised of two or more characteristic decays, increasing the pulse duration will enhance the longer components relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…A mathematical model for the operation of the double chopper was derived, drawing on prior work by others , (see Supporting Information for details). It showed that the maximum TG emission signal intensity was a compromise between competing factors: faster chopper speeds decreased the delay time and increased the number of TG cycles per image to increase the signal, whereas slower chopper speeds increased the excitation pulse duration and the integration time per TG cycle to increase the signal.…”
Section: Resultsmentioning
confidence: 99%
“…A mathematical model for the operation of the double chopper was derived, drawing on prior work by others , (see Supporting Information for details). It showed that the maximum TG emission signal intensity was a compromise between competing factors: faster chopper speeds decreased the delay time and increased the number of TG cycles per image to increase the signal, whereas slower chopper speeds increased the excitation pulse duration and the integration time per TG cycle to increase the signal.…”
Section: Resultsmentioning
confidence: 99%
“…Despite these efforts, the effects of the excitation and acquisition parameters for intensity-ratiobased phosphor thermometry remain poorly understood. For example, variations in the excitation parameters (pulse energy, wavelength and pulse width) can lead to temperature measurement errors for lifetime-based phosphor thermometry [24][25][26]. However, these excitation effects remain unclear for the intensity-ratio-based method.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of the excitation process on the luminescence emission of phosphors is studied in two other papers. In Allison [10], the effect of excitation pulse duration on the photoluminescence properties of phosphors is investigated. Three different phophors, Mg 4 FGeO 6 :Mn, La 2 O 2 S:Eu, and YAG:Dy were excited by diode laser pulses at different wavelengths in the µs to ms range and the temporal emission characteristics are recorded by a photomultiplier.…”
mentioning
confidence: 99%